Pengembangan Ekonomi Kreatif Batik Tulis Pamekasan Upaya Peningkatan Ekonomi Masyakat Persepektif Ekonomi Islam - Maulidi Maulidi (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Development economy creative have very important role in development economy society Creative economy in field based crafts _ legacy culture that is batik crafts . Challenge the largest written batik entrepreneurs in this era is how guard sustainability a works so no the more thinning and undermined by its tightness competition batik industry.Because More the year of written batik the more thinning , remember rampant more batik printing products affordable from facet price and more fast the workmanship. There is empowerment based economy capable creative _ give gradual and continuous motivation , training and coaching to society . activity training this is effort for empower economy creative in the district pamekasan In particular in the village that incidentally batik production so capable Upgrade economy community and management of written batik as product economy creative which continues to be preserved . Type research used _ in study this is research field ( field research ). Aim study this is for knowing so far where is understanding Public about economy majority creative profession as written batik craftsmen . Method which used in study this is qualitative, with tool collectors data as following : interview deep,observation and documentation,From the results study districts pamekasan could Upgrade income Public but must sharia principles , besides it's a training program that is given government districts through each district because could add outlook as well as experience for participating participants _ training it this _ seen of 15 people who follow program training and all which implement activity processing of written batik as well as media management Meanwhile in Economic review . Keywords : Creative Economy Batik Written _ effort enhancement economy society